The New College English Teaching Reform in NCEPU: A Teaching Experiment - Ren, Junhong; Wang, Na (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Level-based College English teaching has lost its appeal in North China Electric Power University. To stimulate students’ motivation in college English learning, a new teaching reform under the production-oriented approach is initiated. In the teaching experiment, we took reforms in teaching materials, teaching process and assessment. Subsequent questionnaire indicates that students hold positive attitudes toward this new teaching approach. However, alteration needs to be made in order to guarantee better teaching results.